Structural Employment Challenges and Digital Economy Dynamics in Kenya Pathways to Inclusive and Decent Work - Mungai, David; Maina, Ivy Wanjiku (Business and Investment Review, 2025)
Kenya’s labor market in 2024–2025 reflects a structural paradox: sustained economic growth alongside limited progress in generating formal, high-quality employment. While total employment rose to approximately 20.8 million, nearly 90% of new jobs were informal, constraining productivity and social protection coverage. Youth unemployment and NEET rates remain elevated, signaling systemic risks to human capital development. Concurrently, the digital economy is reshaping labor dynamics, creating opportunities through fintech, e-commerce, and gig platforms, yet introducing vulnerabilities such as income volatility, algorithmic control, and regulatory gaps. This study employs a descriptive-analytical approach using secondary data from KNBS, Central Bank of Kenya, and international policy reports to examine employment trends, sectoral drivers, and digitalization impacts. Findings indicate that Kenya’s employment challenge is structural rather than cyclical, requiring integrated reforms that combine sectoral productivity upgrading, demand-linked skills development, and labor-market governance modernization. Policy recommendations emphasize leveraging the Digital Economy Blueprint to formalize MSMEs, expand digital skills, and extend social protection to platform workers, thereby aligning technological transformation with inclusive, decent work outcomes.